Carbon catabolite repression occurrence in photo fermentation of ethanol-rich substrates. (1st November 2021) - Policastro, Grazia; Giugliano, Marco; Luongo, Vincenzo; Napolitano, Raffaele; Fabbricino, Massimiliano
Abstract: The paper investigates the phenomenon of Carbon Catabolite Repression occurring during photo fermentation of ethanol-rich effluents, which usually contain ethanol as main carbon source, and glycerol as secondary one. The study was conducted using mixed phototrophic cultures, adopting, as substrate, the effluent produced by the alcoholic fermentation of sugar cane bagasse. In order to elucidate the phenomenon, experimental tests were carried out using two different ethanol to glycerol ratios. Results were compared with those resulting from pure ethanol and glycerol conversion. According to the obtained data, as a result of Carbon Catabolite Repression occurrence, the presence of glycerol negatively affects hydrogen production. Indeed, part of the ethanol source is converted to biomass and polyhydroxybutyrate rather than to hydrogen. In more details, the presence of glycerol determines a drop of the hydrogen production, which goes from 12 % to 32 %, according to the ethanol/glycerol ratio, compared to the production obtained from fermentation of ethanol alone. Therefore, to promote the hydrogen production, it is advisable to apply strategies to produce low glycerol concentrations in the ethanol production stage. Highlights: Photo fermentation was applied to ethanol-rich fermentation effluents. The presence of glycerol in ethanol-rich effluents generates the CCR phenomenon. The coexistence of ethanol and glycerol promotes biomass and PHB production. Higher glycerol concentration determines a lowering of the hydrogen yield. The use of mixed phototrophic cultures enhances the hydrogen yield.